Cholinesterase Inhibitor 6-Chlorotacrine - In Vivo Toxicological Profile and Behavioural Effects - Misik, Jan; Nepovimova, Eugenie; Pejchal, Jaroslav; Kassa, Jiri; Korabecny, Jan; Soukup, Ondrej (Current Alzheimer Research, 2018)
Background: 6-chlorotacrine is a cholinesterase inhibitor showing good inhibitory potential, even better than parent compound tacrine, in vitro. Despite tacrine scaffold is broadly used for design and synthesis of novel compounds with anti-Alzheimer's potential, no in vivo effects have been investigated so far. Thus, basic toxicological and behavioural evaluation has been carried out throughout this study. Methods: Maximum tolerated dose (MTD) and median lethal dose (LD50) were assessed in BALB/c mice and Wistar rats. Behavioural effects were observed in rats performing the multiple T-maze test, the water maze test and the step-through passive avoidance test. All outcomes were compared with the effects of parent compound - tacrine. Results: The toxicity of 6-chlorotacrine was increased compared to tacrine with MTD 6.0/5.0 mg.kg-1 (i.m., male/female mice), 6.0/5.0 mg.kg-1 (i.p., male/female rats) and LD50 9.0 mg.kg-1 (male rats). At MTD doses, no histopathological changes and blood biochemistry abnormalities were observed except decreased plasma creatinine levels. 6-chlorotacrine showed good effects in the reversal of quinuclidinyl benzilate-induced amnesia. Best results were achieved at the dose of 1.8 mg.kg-1 (20% LD50) in the water maze test; the pro-cognitive effect was stronger than that of tacrine (5.2 mg.kg-1, 20% LD50). Other doses tested (0.9 mg.kg-1 and 2.7 mg.kg-1) showed similar effects as tacrine in the water maze, multiple T-maze and passive avoidance test. Conclusion: Observed effects predetermined 6-chlorotacrine as a potent parent compound for the synthesis of novel multifactorial drugs intended to the treatment of Alzheimer's disease. Even though 6- chlorotacrine showed in vivo beneficial effect with no signs of toxicity, further tests on the field of biochemistry and pharmacology are essential to disclose the exact mechanism of action, safety evaluation and the metabolic fate of the compound after the repeated administration.
Keywords: water maze